Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Fuchs, Sven (2023)
ABSTRACT: Since 1963, the International Heat Flow Commission has been fostering the compilation of the Global Heat Flow Database to provide reliable heat-flow data. Over time, techniques and methodologies evolved, calling for a reorganization of the database structure and for a reassessment of stored heat-flow data. Here, we provide the results of a collaborative, community-driven approach to set-up a new, quality-approved global heat-flow database. We present background information on how heat-flow is determined and how this important ther-mal parameter could be systematically evaluated. The latter requires appropriate documentation of metadata to allow the application of a consistent evaluation scheme. The knowledge of basic data (name and coordinates of the site, depth range of temperature measurements, etc.), details on temperature and thermal-conductivity data and possible perturbing effects need to be given. The proposed heat-flow quality evaluation scheme can discriminate between different quality aspects affecting heat flow: numerical uncertainties, methodological uncertainties, and environmental effects. The resulting quality codes allow the evaluation of every stored heat -flow data entry. If mandatory basic data are missing, the entry is marked accordingly. In cases where more than one heat-flow determination is presented for one specific site, and all of them are considered for the site, the poorest evaluation score is inherited to the site level. The required data and the proposed scheme are presented in this paper. Due to the requirements of the newly developed evaluation scheme, the database structure as presented in 2021 has been updated and is available in the appendix of this paper. The new quality scheme will allow a comprehensible evaluation of the stored heat-flow data for the first time.